Technological Advances in Huanglongbing (HLB) or Citrus Greening Disease Management - Paudyal, Krishna Prasad (Journal of Nepal Agricultural Research Council, 2016)
Huanglongbing (HLB), previously citrus greening disease, is the most destructive of citrus species causing major threat to the world citrus industry. The disease was reported from China in 1919 and now known to occur in more than 40 different countries of Asia, Africa, South and North America. Three species of gram negative bacterium namely Candidatus Liberibacter asiaticus, Candidatus Liberibacter africanus and Candidatus Liberibacter americanus are the casual organisms of HLB, respectively prevailing in the continent of Asia, Africa and South America. It is one of the most extensively researched subjects in citriculture world. HLB was detected in 2004 and 2005, respectively in San Paulo of Brazil and Florida of USA: the two leading citrus production hub of the world causing huge economic loss within 5 years of first detection. Since then research on HLB detection and management was further accelerated in American continents. This paper presents the scientific advancement made on detection, spread, economic losses caused by HLB in different parts of the world and controlling management strategies. Remarkable achievements have been made on HLB detection techniques including iodine test, qPCR and more recently in spectroscopy. While efforts are being made to develop resistance varieties using conventional and biotechnological tools management strategy which includes reduction of inoculums source, vector control and replant with disease-free planting materials still remains major option for HLB control. Citrus intercropping with guava have shown promising results for vector reduction. Journal of Nepal Agricultural Research Council Vol.1 2015, pp.41-50